#CancelCulture: examining definitions and motivations - Tandoc, Edson C. (2022)
While cancel culture has become a social media buzzword, scholarly understanding of this phenomenon is still at its nascent stage. To contribute to a more nuanced understanding of cancel culture, this study uses a sequential exploratory mixed-methods approach by starting with in-depth interviews with social media users (n = 20) followed by a national online survey (n = 786) in Singapore. Through the interviews, we found that our participants understand cancel culture as more than just a mob engaged in public shaming on social media; it also involves perceptions of power imbalance and social justice. Building on these perspectives from our interviews, we tested the framework of theory of planned behavior in predicting intention to engage in cancel culture and expanded it by examining the effects of people’s belief in a just world using an online national survey in Singapore. The analysis showed that attitude, subjective norms and perceived behavioral control were positively related to intention to engage in cancel culture, while general belief in a just world was a negative predictor.